Mediation behaviour : why we act like we do - Walker, Stephen (London : Bloomsbury Publishing, 2021)
"Logical or psycho-logical? Which are we when making decisions and negotiating at mediation? We go to mediation to make peace yet prepare for war. Why? What makes us self-sabotage? Learn which behaviours are obstacles to settlement and how to overcome them. Find out how to apply the latest research in neuroscience, behavioural economics and psychology to achieve better outcomes. Our heads, heartsand guts - which should we use and when? More than an update and discussion of the latest research findings, Mediation Behaviour: Why We Act Like We Do is experience-based and using that shows how to resolve disputes successfully and cost-effectively. Written from the point of the view of mediators, disputing parties, their advisers and representatives, this new title: Investigates the role of emotions, cognitive biases and intuitions in our mediation behaviour Identifies the behaviours that are barriers to settlement and the ones that are bridges to settlement Shows how they affect the six mediation fundamentals: self, money, power, fairness, truth and trust Explains how to be better at negotiation, risk analysis and persuasion Looks in detail at the psychology of offers - how to make them and how to reject them Explores how mediating online changes the way we do things This book is an indispensable resource for mediators, advocates, representatives - both lawyers and non-lawyers - clients, experts, and anyone involved in conflict and conflict management"--
Chapter 1 Introduction -- Chapter 2 The Brain -- Chapter 3 Feeling: Emotions -- Chapter 4 Thinking: Cognitive Biases and Mind Traps -- Chapter 5 Intuition -- Chapter 6 Self -- Chapter 7 Frequently Observed behaviours (FOBs): Barriers -- Chapter 8 Frequently Observed behaviours (FOBs): Bridges -- Chapter 9 Persuasion -- Chapter 10 Prediction -- Chapter 11 Perception -- Chapter 12 Money -- Chapter 13 Power -- Chapter 14 Truth -- Chapter 15 Fairness -- Chapter 16 Trust -- Chapter 17 The Psychology of Offers -- Chapter 18 Online mediation.
Includes index.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily.
Keywords: Conflict management; Mediation; Conflict management -- Psychological aspects; Mediation -- Psychological aspects